2019
DOI: 10.1029/2018tc005200
|View full text |Cite
|
Sign up to set email alerts
|

Multiproxy Isotopic and Geochemical Analysis of the Siwalik Sediments in NW India: Implication for the Late Cenozoic Tectonic Evolution of the Himalaya

Abstract: Provenance analysis of the Sub-Himalayan Late Miocene-Pleistocene foreland basin deposits (Siwaliks) from the Dehradun reentrant area provides a 10-Myr long record of the denudation history and tectonic evolution of the northwestern Indian Himalaya. We studied Siwalik sediments exposed along the Mohand-Rao and Haripur-Khol sections, using detrital zircon U-Pb geochronology, major and trace elements, and Sr-Nd isotope geochemistry. Results suggest that the erosion pattern has been relatively stable since the La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 122 publications
6
37
0
Order By: Relevance
“…To reconstruct palaeodenudation rates from in situ cosmogenic 10 Be analyses of foreland sediments, it is, therefore, critical to trace potentially recycled sediments. In the Himalayas, although Sr-Nd isotopes have been widely used to study sediment provenance, our results and those of Mandal et al (2019) suggest that these geochemical proxies are insensitive to sediment recycling, which is better identified by simpler major and trace element analyses, notably Al/Si and Na/Si, which are linked to weathering and sorting processes, respectively Lupker et al, 2011).…”
Section: Robustness Of the Reconstructed 10mentioning
confidence: 64%
“…To reconstruct palaeodenudation rates from in situ cosmogenic 10 Be analyses of foreland sediments, it is, therefore, critical to trace potentially recycled sediments. In the Himalayas, although Sr-Nd isotopes have been widely used to study sediment provenance, our results and those of Mandal et al (2019) suggest that these geochemical proxies are insensitive to sediment recycling, which is better identified by simpler major and trace element analyses, notably Al/Si and Na/Si, which are linked to weathering and sorting processes, respectively Lupker et al, 2011).…”
Section: Robustness Of the Reconstructed 10mentioning
confidence: 64%
“…No significant increase in the relative proportion of 1,700–1,900‐Ma grains is observed throughout these lower to middle Miocene sections, indicating that the iLH had yet to significantly breach the surface at this time. However, compilation of new and recently published detrital zircon U‐Pb ages from the middle to upper Siwalik Group within the Dehradun reentrant reveal a significant increase in abundance of 1,700–1,900‐Ma grains when compared to lower to middle Miocene foreland basin results (Figure ), providing compelling evidence that iLH unroofing initiated by at least ~7–10 Ma in NW India (Mandal et al, ). This is further supported by a similar shift in provenance documented within the Siwalik Group in Nepal (Bernet et al, ; DeCelles et al, ; Najman et al, ).…”
Section: Discussionmentioning
confidence: 77%
“…Detrital zircon U‐Pb ages results from all samples collected within the ~3‐km‐thick package of lower to middle Miocene foreland basin deposits of NW India showed minimal variation (Figure S5), and Figure shows a compilation of these data for simplicity. New detrital zircon U‐Pb ages from one sample of the upper Siwalik Group (15HP80) were compiled with published ages from middle‐upper Siwalik group of the Dehradun reeantrant (Mandal et al, ), and these data revealed a significant increase in the abundance of ~1,700–1,900‐Ma grains with an increase in the abundance of grains younger than ~400 Ma when compared to the age distribution of lower to middle Miocene deposits (Figure ). For detailed explanations of sample localities and individual sample results, we refer the reader to the supporting information.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations